Contributions to an interpretation of the structure of Dasein according to its bidimensional character - Basso Monteverde, Leticia (2014)
From a reading of Sein und Zeit and contemporary courses, we are interested in examining the transcendental structure of Dasein to explain what we understand as its bidimensional character. For this, we analyze the function of the mood in the dynamics of the structure through the anxiety (Angst) and profound boredom (tiefe Langeweile). We emphasize the affective disposition as an existential starting point and condition of possibility for  two  pathways,  since  in  relation  to  being  we  observed  tension  between two dimensions that are oscillated Dasein towards one concealment and one unconcealed motion of what happens. With this interpretation we intend to show that the tensive dynamics of the bidimensional structure of Dasein proposed here is the effect of the original givenness of being.